RETRACTED: Sirtuin1 Role in the Melatonin Protective Effects Against Obesity-Related Heart Injury - Favero, Gaia; Franco, Caterina; Stacchiotti, Alessandra; Rodella, Luigi Fabrizio; Rezzani, Rita (Frontiers in Physiology, 2020)
Obesity is actually a worldwide epidemic disease that induces important heart structural and functional changes and predisposes to devastating cardiac complications. Sirtuin1 has been found to regulate also cardiac function, but its role in cardioprotection is not fully elucidated. The aims of the present study was to determine whether melatonin, modulating sirtuin1, may alleviate obesity-induced cardiac dysfunctions and evaluate in deep its related signaling(s) of action. In the present study were investigated 10 lean control mice and 10 leptin-deficient obese mice (ob/ob) orally supplemented with melatonin for 8 weeks, as well as equal numbers of age-matched untreated lean and ob/ob mice. Heart morphology, the involvement of sirtuin1 activity and the expression of markers of mitochondria biogenesis, oxidative stress and inflammation were evaluated at heart level. We firstly observed in untreated ob/ob mice significant heart hypertrophy, reduced sirtuin1 activity, altered oxidative balance and overexpression of inflammatory markers. Notably, melatonin supplementation in ob/ob mice restored sirtuin1 activity and so restored heart morphology and a correct oxidative balance through also mitochondrial signalling that, in turn, reduced inflammation. In the present study, we observed that sirtuin1 appears central in the cellular and molecular mechanisms of action of melatonin, collectively to the numerous cytoprotective capacity of this multitasking indoleamine. The activation of the cardiac sirtuin1- and mitochondrial-correlated pathways is central to rebuffing oxidative stress, inflammation and so heart remodelling caused by obesity and thus melatonin may represent a promising cardiac protective approach against obesogenic related injury.